THE ROLE OF ACCOUNTING CONSERVATISM, LEVERAGE AND FIRM SIZE ON THE QUALITY OF BANKING PROFITS IN INDONESIA - Rochman Arif ,; Bandi , Bandi; Agung Nur Probohudono ,; Djuminah, Djuminah (Jurnal Cakrawala Ilmiah, 2025)
This study aims to determine the Effect of Accounting Conservatism, Leverage, and Company Size on Earnings Quality in banking companies in Indonesia. The population of this study is all banking companies listed on the Indonesia Stock Exchange for the 2019-2023 period, totaling 47 companies. Sample selection through the Purposive Sampling method. There are 229 observation data. The data analysis technique used is descriptive analysis, panel data regression analysis and hypotheses are tested using Stata 17. The results of this study indicate that Accounting Conservatism does not have a significant effect on Earnings Quality. Leverage has a negative effect on Earnings Quality, and Company Size does not have a significant effect on Earnings Quality